Implementasi Pendidikan Karakter Profil Pelajar Pancasila dalam Kurikulum Merdeka Di SDN 1 Tombatu - Natalya Tirsa Mokorowu; Deitje A.Katuuk; Deysti T. Tarusu; Richard D. H. Pangkey (Jurnal Elementaria Edukasia, 2023)
ABSTRACT Character education is a demand that continues to be voiced in the world of education today, because it not only has an impact on individuals in developing their potential but also has an impact on institutions and even society in general. This research aims to find the implementation of Pancasila student profile character education in the Merdeka Curriculum at SDN 1 Tombatu. This research uses qualitative study research with a phenomenological approach, namely the researcher looks and hears more deeply about individual understandings and opinions about experiences related to the material used as a reference for the research. Data collection techniques use observation techniques and structured and unstructured interviews. The results obtained in the research at SDN 1 Tombatu were carried out in accordance with the six dimensions of the Pancasila Student Profile, namely faith and devotion to God Almighty and noble character, global diversity, mutual cooperation, independence, critical reasoning and creativity.